MENINGKATKAN HASIL BELAJAR SISWA PADA TEMA PERISTIWA DALAM KEHIDUPAN MENGGUNAKAN MODEL PEMBELAJARAN DISCOVERY LEARNING - Almughnin, Nazla Rahmatika (Jurnal Al-Fatih, 2024)
The background of this research is due to the lack of interest in learning among students. In fact, learning interest is a determining factor in achieving learning objectives. The research method used is the classroom action research method, by directly observing how the teacher conducts the learning process at MIN 2 Labuhanbatu Utara, particularly in class V, in efforts to improve learning outcomes through discovery learning. Additionally, to gather more information, the researcher used interview methods as a medium for collecting other information. The results of this study indicate that before using the discovery learning model on the theme of events in life, out of 30 students, only 23.33% or 7 students achieved passing grades, while 76.66% of students or 23 students did not. After using the discovery learning model, the number of students who have been able to fully understand the lesson material reaches 90% or 27 people, and only about 3 people or 10% have not yet understood the material. Therefore, it can be stated that the discovery learning model is effective in improving students' learning outcomes.